Disseminated Talaromyces marneffei infection after renal transplantation: A case report and literature review - Xu, Liang; Chen, Xiuxiu; Yang, Xuying; Jiang, Hongtao; Wang, Jianli; Chen, Shaowen; Xu, Jian (Frontiers in Cellular and Infection Microbiology, 2023)
We reported a 31-year-old man who received renal transplantation for more than 2 years. He was admitted to our hospital on 9 March 2022 due to intermittent diarrhea accompanied by leukopenia for more than 1 month. The patient successively developed high fever, cough, anemia, weight loss, gastrointestinal bleeding, and liver function impairment. Computed tomography (CT) revealed a slight inflammation in the lower lobes of both lungs, enlargement of the lymph nodes in the retroperitoneal and the root of mesenteric areas, and hepatosplenomegaly. Talaromyces marneffei was detected by metagenomics next-generation sequencing (mNGS) in blood and bronchoalveolar lavage fluid, and the pathogen was subsequently verified by blood culture. After endoscopic hemostatic therapy and antifungal therapy with voriconazole and amphotericin B cholesteryl sulfate complex, the patient was successfully discharged. Oral voriconazole was given regularly after discharge. Diarrhea, fever, enlargement of the lymph nodes, and endoscopic evidence of erosion may indicate intestinal T. marneffei infection. Although the mortality of T. marneffei infection after renal transplantation is very high, timely and effective antifungal therapy with amphotericin B cholesteryl sulfate complex is still expected to improve its prognosis.